Sliding mode control for autonomous vehicles with long delay to track straight paths - García Gabín, winston; Zambrano, Darine; Camacho, Osear (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper is presented the application of Sliding Mode Controller in autonomous vehicles with long dead time to track straight paths. The proposed controller is synthesized from a general reduced order model of the robot. This approach makes possible the application of this controller to different kind of robots, if they can be approximated by that kind of model. Based on computer simulations the proposed controller is compared against feedback state and lateral feedback position controllers. The robot model used is a cinematic one corresponding with a tricycle type model. The results show that the proposed approach presents better performance than the other two.